On the ‘Female Gaze’ in the Interview Setting: Methodological Insights From Fieldwork With Women - Piazzesi, Chiara (Italian Sociological Review, 2024)
Building on a constructivist understanding of the interview techniques common to the social sciences, in this paper I discuss and analyse through a feminist sociological lens the interview setting that I built and experienced during two years of fieldwork with a small sample of Canadian women. Relevant conversational gestures exchanged in such a setting usually encompass verbal and bodily cues, but what principally concerns me here is a further aspect of the interview setting: namely, its visuality, and the related act of gazing carried out by the (female) participants. Using the concept of the ‘female gaze’ (Riley et al., 2016) – i.e., the self-assessing, judgemental gaze that women direct at one another and at themselves in postfeminist contexts – I offer salient examples from my fieldwork in order to show the ways in which the female gaze shaped my understanding of how women look at themselves and at each other (including at me, as interviewer), both in person and in pictures. My goal is to analyse gazing as a competence, and more specifically as a structured and regulated female competence in postfeminist culture, but also to bring a greater reflexivity to bear on the embodied experience of fieldwork (Oakley, 1981; Pillow, 1997). As I came to learn in the course of this project, the act of gazing while conversing, accompanied by the corresponding verbal cues, played a crucial, if unexpected and unplanned, role in data production and in my subsequent choice of research questions.